REHABILITASI MEDIK PADA SKOLIOSIS - Pelealu, Jane; Angliadi, Leonard S.; Angliadi, Engeline (UNIVERSITAS SAM RATULANGI, 2014)
Abstract: Scoliosis is one of the spine deformities in which a personâ€™s spine is bend laterally associated with or without a rotation of the vertebrae. There are several variations in the etiology, onset, prognosis, and therapy of scoliosis, but the effects of untreated scoliosis are the same, as follows: pain, and disturbances in balance, cardiopulmonal function, emotion, behaviour, and ADLs (activities in daily living). The most common symptoms of scoliosis are abnormal deformity of spine which can cause pain, decrease of quality of life, disability, comestic disturbance, functional limitation, pulmonary problems, probabilty of progression at adulthood, dan pyschological disturbance. In physical examination, midline shift of spinous process, asymmetry of the back, rib hump, asymmetry of the scapula, hip, shoulder and pelvis, as well as leg length discrepancy must be carefully examined. Besides that, a radiological examination showing the Cobb angle is also important to do. The therapy of scoliosis includes observation, rehabilitation therapy namely physical modalities, orthoses/brace, exercise, or invasive therapy such as operation. Additionally, the prognosis of scoliosis depends on sex, curve angle at first recognition, type and rotation of curve, and age of onset.Keywords: scoliosis, spine, rehabilitation, exercise, orthosesÂ Â Abstrak: Skoliosis adalah deformitas tulang belakang yang ditandai oleh lengkungan ke lateral dengan atau tanpa rotasi tulang belakang. Etiologi, onset, prognosis, dan terapi skoliosis dapat bervariasi, namun akibat skoliosis yang tidak diterapi sama, yaitu nyeri, yang disertai gangguan dalam keseimbangan, fungsi kardiopulmonal, emosional dan perilaku, serta aktivitas kehidupan sehari-hari (AKS). Gejala yang paling umum dari skoliosis ialah adanya suatu lekukan yang tidak normal dari tulang belakang yang dapat berakibat nyeri, penurunan kualitas hidup dan disabilitas, deformitas yang mengganggu secara kosmetik, hambatan fungsional, masalah paru, kemungkinan terjadinya progresifitas saat dewasa, dan gangguan psikologis. Hal-hal yang harus diperhatikan pada pemeriksaan fisik ialah deviasi prosesus spinosus dari garis tengah, punggung yang tampak miring, rib hump, asimetri dari skapula, pinggul, bagian atas dan bawah trunkus (bahu dan pelvis), serta perbedaan panjang tungkai. Selain itu, pemeriksaan radiologik untuk melihat sudut Cobb juga penting untuk dilakukan. Terapi skoliosis dapat berupa observasi, terapi rehabilitasi yaitu pemberian modalitas, ortosis/brace, latihan, atau terapi invasif seperti operasi. Prognosis skoliosis dipengaruhi oleh jenis kelamin, ukuran kurva saat pertama kali ditemukan, tipe dan rotasi kurvatura dan usia saat onset skoliosis.Kata kunci : skoliosis, tulang belakang, rehabilitasi, latihan, ortosis